1986
DOI: 10.1159/000469343
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Human Placental Microsomal Aminopeptidase: Immunological Difference between Placental Microsomal Aminopeptidase and Pregnancy Serum Cystyl-Aminopeptidase

Abstract: Human placental microsomal aminopeptidase (microsomal PAP) was purified 3,880-fold from human placenta and characterized. The enzyme was solubilized from membrane fractions with Triton X-100 and also trypsin digestion, and subjected to zinc sulfate fractionation, chromatographies with DE-52, hydroxylapatite, Sephacryl S-300 and lentil lectin- Sepharose 4B, and finally affinity chromatography with bestatin-Sepharose 4B. Microsomal PAP was separated from aminopeptidase A (AAP) by affinity chromatography. The app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

1988
1988
1994
1994

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…Regoli and Drapeau, Sherbrooke University, Sherbrooke, Quebec). Purified AmM (AmM) and AmM antisera were prepared by one of us (Dr. Mizutani) as previously described (27).…”
Section: Methodsmentioning
confidence: 99%
“…Regoli and Drapeau, Sherbrooke University, Sherbrooke, Quebec). Purified AmM (AmM) and AmM antisera were prepared by one of us (Dr. Mizutani) as previously described (27).…”
Section: Methodsmentioning
confidence: 99%
“…Human alanine aminopeptidase has been found to be ptesent in virtually all tissues Studieid, with relatively high specific activities in the brush border membranes of kidney proximal tubules and intestine and in bile canalicular membranes (21 -27). Human alanine aminopeptidase has been purified from liver (8, 12, 28 -30), kidney (11,(31)(32)(33), intestine (13,34,35), placenta (31,36) and blood plasma (37,38). Relative molecular mass estimations of the enzyme range from about 150000 (39-41) (obtained by electrophoresis of the non-purified serum enzyme) to about 240 000 for purified enzymes by gel filtration (16,28,42).…”
Section: Alanine Aminopeptidasementioning
confidence: 99%
“…One difference between the two purified preparations was the relatively high alanyl-ß-naphthylamidase acitivity of the placental enzyme preparation. The preferential hydrolysis of leucylarylamides by cystyl aminopeptidase is a general finding (36,38,40,48,56). Some characteristic properties of cystyl aminopeptidase which distinguish it from some other aminopeptidases, are its heat lability and resistance to methionine, bestatin and amastatin inhibition (15,57).…”
Section: Cystyl Aminopeptidasementioning
confidence: 99%
See 1 more Smart Citation
“…We purified this enzyme from human placental microsomal fractions [6]. We used immobilized bestatin, the product of streptomyces, which is a powerful inhibitor of aminopeptidases N and B, for the affinity column in the purification of this enzyme [7]. Molecular cloning showed that AP-N is identical to the cell surface cluster of the differentiation antigen (CD13) [8].…”
mentioning
confidence: 99%